SpinelViz: An interactive 3D application for visualizing spinel group minerals - Ganuza, María Luján (2012)
SpinelViz is an application for the visualization of the spinel group minerals in three dimensions. SpinelViz uses the spinel prism to display mineral composition datasets from different tectonic settings. The application projects data onto 2D and 3D plots. Such projections are used to classify spinels based on geochemical data. The spinel mineral group exhibits a wide range of solid solutions and has been the subject of many thermodynamic studies. Spinels, particularly chromites from mafic-ultramafic igneous rocks are used to discriminate among various tectonic settings. Their existence in ultramafic rocks and their resistance to alteration make them excellent tectonic tracers and a very important tool in search for economic deposits of the platinum group elements (PGE) and Ni-Cu-PGE. SpinelViz provides a set of functionalities that helps users to manipulate their datasets for both 2D and 3D visualization and 2D projections.